2017
DOI: 10.1002/biot.201700389
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Lifetime and UV‐Vis Spectroscopy to Evaluate the Interactions Between Quercetin and Its Yeast Microcapsule

Abstract: Quercetin is a fragile bioactive compound. Several works have tried to preserve it by encapsulation but the form of encapsulation (mono-or supramolecular structure, tautomeric form), though important for stability and bioavailability, remains unknown. The present work aims at developing a fluorescence lifetime technique to evaluate the structure of quercetin during encapsulation in a vector capsule that has already proven efficiency, yeast cells. Molecular stabilization was observed during a 4-month storage pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…The presence of catechins was further proved by the observation of characteristic peaks at about 270 nm in the UV–vis absorption spectrum (Figure S8). The new emerging peak at about 375 nm might be related to the oxidation of TPs. , The analysis above suggested that the GNPs were successfully prepared by the separated processes and the whole program did not involve harsh chemicals and extra energy inputs.…”
Section: Results and Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The presence of catechins was further proved by the observation of characteristic peaks at about 270 nm in the UV–vis absorption spectrum (Figure S8). The new emerging peak at about 375 nm might be related to the oxidation of TPs. , The analysis above suggested that the GNPs were successfully prepared by the separated processes and the whole program did not involve harsh chemicals and extra energy inputs.…”
Section: Results and Discussionmentioning
confidence: 98%
“…The new emerging peak at about 375 nm might be related to the oxidation of TPs. 47,48 The analysis above suggested that the GNPs were successfully prepared by the separated processes and the whole program did not involve harsh chemicals and extra energy inputs.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In order to further observe the variations in quercetin distribution under different spinning flow rates, fluorescence microscopy was used to analyze the cross section of the fibers. It is known that quercetin presents a strong fluorescence display, whereas the regenerated cellulose does not, allowing the observation of quercetin distribution in fibers using a fluorescence microscope. However, FT-IR and XRD analyses revealed that the chemical structure and crystalline state of quercetin regenerated from [Emim]Ac had undergone changes, resulting in the loss of its fluorescence properties (Figure a).…”
Section: Resultsmentioning
confidence: 99%
“…The cell-based carriers selected in this study include yeast cells (YC), including alive yeast cell carriers (aYC) and deactivated yeast cell carriers (dYC), and yeast cell wall particles (YCWP). Yeast microcarrier and its derivatives are widely accepted encapsulation matrixes for food applications based on their “generally recognized as safe” (GRAS) status. YC and YCWP possess high encapsulation yield for polyphenolic compounds such as curcumin and significantly enhance physicochemical stability as demonstrated in the literature and our recent studies. , Moreover, fungal–bacterial binding interactions are found ubiquitously in the environment and particularly in biofilms. Therefore, based on this background knowledge, this study evaluated the role of these diverse cell carrier compositions derived from yeast cells for the encapsulation of curcumin, binding of cell carrier compositions to biofilms, their efficacy in inactivation of bacteria in the selected biofilm model, and influence on the structure of the biofilm after treatment with the selected compositions. Listeria innocua (ATCC 33090) was selected as a nonpathogenic surrogate for the foodborne pathogen Listeria monocytogenes, which is a serious concern for the food industry based on its ubiquitous presence in the environment and biofilm-forming ability .…”
Section: Introductionmentioning
confidence: 99%